Immediate effect of semioccluded vocal tract therapy on acoustic parameters in the processes of masculinization and feminization of the voice - Fuenzalida Cabezas, Rodrigo; Sandoval Zúñiga, María Soledad; Díaz Sandoval, Eugenia; Pérez Zurita, Tanya; Quiroz Bustamante, Fernanda; Rosales Orellana, Marcela (Revista de Investigación en Logopedia, 2021)
The purpose of this study is to determine, describe and compare the immediate effect of Semioccluded Vocal Tract Therapy (TVSO) on acoustic parameters in the processes of feminization and masculinization of the voice of 40 transsexuals between 18 and 40 years old. It corresponds to a quantitative study, with a preexperimental design with pre and post test, with a dimension of transversal temporality and a descriptive and comparative scope. The instrument used to measure acoustic parameters was the acoustic voice analysis program PRAAT (Boersma and Weenink, 2018). The results indicate that although in the female transsexuals the values ​​of the acoustic parameters decreased; there was only immediate effect in Local Jitter, Jitter APQ5, Harmonic-noise ratio and Fundamental frequency (F0); that shows that the female’s voice became high-pitched. In male transsexuals, F0 was modified after therapy, then the voice became more deep. It is concluded that TVSO therapy has an immediate effect mainly on Jitter and F0 and can be considered an alternative, viable and complementary therapy in the process of masculinization and feminization of voice.